ANALISIS TINGKAT PENCEMARAN AIR BERDASARKAN PARAMETER FISIK DAN KIMIA PADA KOLAM BEKAS PENAMBANGAN PASIR KOTA PALANGKA RAYA - Kemistin Dian Lestari; Dody Ariyantho Kusma Wijaya; Neny Sukmawatie; Saptawartono Saptawartono; Fahrul Indrajaya (Fakultas Teknik Universitas Palangka Raya, 2026)
Sand mining activities can cause environmental changes and reduce water quality in abandoned mining ponds due to alterations in the physical and chemical characteristics of aquatic ecosystems. This study aimed to analyze the level of water pollution in former sand mining ponds located in Kalampangan Village, Palangka Raya City, based on physical and chemical parameters and the Pollution Index (PI). The study employed a quantitative descriptive method using primary data obtained from water quality measurements, including Total Suspended Solids (TSS), Total Dissolved Solids (TDS), pH, copper (Cu), lead (Pb), and Chemical Oxygen Demand (COD). The analysis was conducted by comparing the measurement results with the water quality standards stipulated in Government Regulation Number 22 of 2021 and by calculating the Pollution Index (PI). The results showed that TSS and TDS concentrations complied with the applicable water quality standards, whereas several chemical parameters, including pH, Cu, Pb, and COD, exceeded the established limits. The low pH values indicated acidic water conditions, while the elevated COD levels suggested the presence of organic and inorganic pollutants in the water. Based on the Pollution Index (PI) calculation, all water samples were classified as slightly polluted. Therefore, environmental management measures such as liming, bioremediation, the utilization of aquatic plants, and aeration are recommended to improve water quality in former sand mining ponds.